Assemblage-level responses of Neotropical bats to forest loss and fragmentation - Gamboa Alurralde, Santiago (2021)
Habitat loss and fragmentation are the most important causes of biological diversity loss, changing the properties of the remaining environment. The Neotropical Region is one of the most affected areas due to the conversion of natural habitats into agricultural activities and deforestation. In this region, bats represent almost 50% of all mammal species, reaching the highest taxonomic and functional diversity. Bats are valuable indicators of biodiversity and ecosystem health, but their response to habitat loss and fragmentation was poorly studied in Argentina. The aim of this study was to analyze the response of bat assemblages to habitat alteration in Northwestern Argentina. The specimens were collected in eight different localities, four well-preserved and four disturbed sites of the Yungas Forests. To describe the structure of bat assemblages, rank-abundance curves, species richness and Shannon (H’) and Simpson (D’) diversity indexes were calculated. To test the assemblage variations among sites, PCA and NPMANOVA analysis were performed. After 96 sampling nights, a total of 565 bats from 23 species were captured. A great variation in the assemblage structure was registered, regardless the disturbance level of the sites. These variations were not significantly different according to statistical analysis. The results support the hypothesis that areas with moderate fragmentation can sustain a high diversity of bat species. Moreover, these results showed that consistent responses to landscape composition at the assemblage level are harder to identify in fragmented Neotropical Forests. The responses of bats to habitat alteration tend to be highly species-specific.